Rotten Apples or Rotten System? Media Framing of Political Corruption in New Zealand and Italy. (18th August 2019) - Berti, Carlo
ABSTRACT: Journalism functions as a watchdog against corruption, and contributes to its social construction in public debate. Investigating media representations of corruption is therefore fundamental to understanding how the issue is socially constructed in specific contexts. This study compares the media framing of corruption in two countries characterized by different levels of corruption, New Zealand and Italy. A qualitative framing analysis of the print media coverage of two major corruption scandals in these countries is conducted, integrated with a historical analysis of the coverage of Transparency International's Corruption Perceptions Index over a period of 20 years. The analysis shows that in New Zealand a "corruption as individual crime" frame dominates, characterized by a focus on individual responsibilities in opposition to the integrity of the country. In Italy, a "systemic corruption" frame dominates, characterized by widespread use of personifications, metonymies, and metaphors of corruption. Corruption is personified and often externalized, leading to a dilution of personal responsibility and accountability. These frames are discussed in relation to the potential role of the media in controlling and curbing corruption.